APPLICATION OF LAW AGAINST WOMEN IN CORRUPTION CASES (Case Study of HighCourt DecisionsDKI Jakarta Number 10/PID. SUS-TPK/2021/PT DKI). - Danti Pratiwi; Farhana (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Decision Number 10/PID. SUS-TPK/2021/PT DKI of the Jakarta High Court considers both legal and non-legal factors when handing down a criminal penalty. In order for the panel of judges to assume responsibility for the panel of judges from the court of first instance in relation to the proved elements of the article, it is necessary to use juridical considerations to state agreement with them. In addition, the purpose of using non-juridical factors is to shorten the defendant's sentence. The theory of the creative process and intuition, which is part of Mackenzie's theory, provides the theoretical framework for the factors taken into account when reaching the verdict. This is due to the fact that the issues raised in mitigation are primarily concerned with the Judge's discretion in imposing a criminal charge. The principles of non-discrimination, gender equality, equality before the law, and justice are not upheld in the Jakarta High Court Decision Number 10/PID. SUS-TPK/2021/PT DKI, which upholds criminal imposition. Furthermore, the imposition of a criminal sentence solely based on the defendant's gender violates the third purpose of the Convention on the Elimination of All Forms of Discrimination Against Women, which is to ensure that women's rights are legally protected on an equal footing with men's rights. In addition, pursuant to the criminal imposition theory, which encompasses the theories of retribution, relative or purpose, and combination, the sentence in Decision Number 10/PID. SUS-TPK/2021/PT You might think of DKI as part of the objective or relative theory. Reason being, criminalization serves no purpose in meeting the absolute requirements of justice, as stated in relativity theory. Just as retaliation cannot be useful in and of itself, it can only serve to safeguard society's interests.